2008
DOI: 10.1177/1046878108319930
|View full text |Cite
|
Sign up to set email alerts
|

Orientations to Video Games Among Gender and Age Groups

Abstract: Questionnaires were completed by 5th-, 8th-, and 11th-grade public schools students in rural and suburban school districts and by undergraduates at two universities in the United States (n = 1,242). They were asked about their orientation to video games-the amount of time they played, their motives for doing so, and the game types they preferred-to better understand the context in which effects research might be organized. The conceptual schema for this research was the uses-and-gratifications perspective. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
248
1
27

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 336 publications
(324 citation statements)
references
References 28 publications
(24 reference statements)
25
248
1
27
Order By: Relevance
“…For example, children under 10 are less able to process plot features, and may become more interested in and able to follow complex storylines as preteens or teens (Greenberg et al, 2008). This is why a 10-year-old may view and interact with Grand Theft Auto as simply a driving game.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, children under 10 are less able to process plot features, and may become more interested in and able to follow complex storylines as preteens or teens (Greenberg et al, 2008). This is why a 10-year-old may view and interact with Grand Theft Auto as simply a driving game.…”
Section: Discussionmentioning
confidence: 99%
“…However, over half (61%) of girls in our survey who regularly played video games enjoyed competition, including 28% who strongly agreed with this reason for play. Greenberg et al (2008) surveyed students of various age groups, ranging from fifth graders to college undergraduates. They found that motivations for game play varied by age or developmental stage.…”
Section: A Focus For Hanging Outmentioning
confidence: 99%
See 1 more Smart Citation
“…Students in their early teens and male students (Greenberg et al, 2010) tend to be more predisposed towards the use of video games in lessons. Some students have expressed extreme boredom when using computers at school, which is mainly used for word processing (McFarlane et al, 2002).…”
Section: Video Games In the Classroommentioning
confidence: 99%
“…In fact, according to Theory of Reasoned Action (Ajzen & Fishbein, 1980), it is thought that belief (i.e., an individual's subjective knowledge and the perceived costs and benefits of the behavior) influences attitude (i.e., an individual's positive and negative feelings about a particular behavior), that in turn shapes behavioral intention. In fact, research has found that adolescents perceive video gaming as a (i) social tool that allows boys to work cooperatively with peers (Olson, Kutner, & Warner, 2008), (ii) way to compete (Greenberg, Sherry, Lachlan, Lucas, & Holmstrom, 2010), and (iii) way express fantasies of power, when boys gain status among peers by owning or mastering these popular games (Olson, Kutner, & Warner, 2008;see Olson, 2010, for a review).…”
Section: Introductionmentioning
confidence: 99%